Laser Iridotomy for Pupillary Block in Children with Endogenous Uveitis - N. N. Arestova; L. A. Katargina; E. V. Denisova; T. B. Kruglova; N. S. Egiyan (Oftalʹmologiâ)
Objective. Development of a differential approach to laser iridotomy in children with endogenous uveitis considering iris characteristics and the reaction of children’s eyes to different laser types.Patients and methods. Thirty-six laser iridotomies were conducted in 36 children aged 8–16 years with pupillary block. Nidek YAG laser was used in YAG (1064 nm) and SLT (532 nm) modes.Results. The frequency of hemorrhagic complications during surgery decreased to 19.4 % since 2009. The frequency of exudative reactions and proliferative syndrome with closure of laser coloboms in 1-6 months after surgery decreased to 33.3 % (25.7 % and 40.9 % respectively).Conclusion. We recommended the patented differential approach for effective nontraumatic laser iridotomy in children with endogenous uveitis. In a thin iris single-stage YAG laser perforation should be performed in maximum bombe and multiple perforation in cases of multi-chamber bombe. In a dense thick iris or in cases of former iridotomy closure two-stage approach should be performed. First, circular coagulation should be done in the form of a ring or spot at the site of the planned coloboma. Second, YAG-laser perforation should be done in 10–14 days. The iris vessels topography, reflexogenic zones, and the peculiarities of the iris reactions to the lasers in children with endogenous uveitis should be considered when choosing a place for a coloboma. The use of thermal coagulating lasers should be limited, especially on thin irises. Active anti-inflammatory therapy and eye monitoring are necessary after laser surgery. The differential approach is safe, effective, and can be recommended for implementation in the practice of pediatric ophthalmology.